2016
DOI: 10.1096/fj.201600332r
|View full text |Cite
|
Sign up to set email alerts
|

Methyl donor deficiency impairs bone developmentviaperoxisome proliferator‐activated receptor‐γ coactivator‐1α–dependent vitamin D receptor pathway

Abstract: Deficiency in methyl donor (folate and vitamin B) and in vitamin D is independently associated with altered bone development. Previously, methyl donor deficiency (MDD) was shown to weaken the activity of nuclear receptor coactivator, peroxisome proliferator-activated receptor-γ coactivator-1α (PGC1α), for nuclear signaling in rat pups, including estrogen receptor-α and estrogen-related receptor-α; its effect on vitamin D receptor (VDR) signaling, however, is unknown. We studied bone development under MDD in ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Furthermore, cathelicidin has been shown to activate TLR4 signaling and modulate inflammatory status in vivo [47]. Though it is still unclear how MS mediated the restorative effect of VD status among offspring, folate and vitamin B 12 deficiencies have been shown to suppress VDR protein levels in bone cells in vitro [28]. This may indicate a critical role of MS nutrients in mediating VD signaling and subsequent inflammatory responses among the offspring.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, cathelicidin has been shown to activate TLR4 signaling and modulate inflammatory status in vivo [47]. Though it is still unclear how MS mediated the restorative effect of VD status among offspring, folate and vitamin B 12 deficiencies have been shown to suppress VDR protein levels in bone cells in vitro [28]. This may indicate a critical role of MS nutrients in mediating VD signaling and subsequent inflammatory responses among the offspring.…”
Section: Discussionmentioning
confidence: 99%
“…A recent European prospective cohort study reported a diet rich in methyl-donor nutrients, such as folate, vitamin B 12 , choline, methionine, and betaine, was associated with global methylation changes [26], which were linked to risks of cardiometabolic diseases among offspring [27]. Previously, an in vivo rat study showed that maternal methyldonor nutrient deficiency downregulated the gene expression of VDR and reduced the bioavailability of active VD [28]. However, the role of methyl-donor nutrients in modulating methylation status of VD-related genes under obesogenic environment remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence shows a direct and indirect connection of vitamin D and SIRT1, where direct influence exists, on the one hand, through binding of VDR to SIRT1 promoter or to SIRT1 and other proteins in a transcription complex [ 3 , 7 , 13 , 207 , 209 , 216 , 217 , 218 ] and, on the other hand, through epigenetic modifications, by regulating each other [ 13 , 32 , 219 ]. The indirect routes involve activation of signaling pathways by molecules such as adiponectin, AMPK, resveratrol, methyl-donors, etc., which upregulate/activate either SIRT1 or vitamin D pathways [ 8 , 49 , 96 , 220 , 221 , 222 , 223 , 224 ]. We briefly summarize the possible interaction of vitamin D and SIRT1 in relation to the regulation of signaling pathways and targeted molecules in Figure 2 .…”
Section: Cooperation Of Vitamin D and Sirt1 Pathwaysmentioning
confidence: 99%
“…In young rats, MDD decreases the total body bone mineral density, reduced tibia length and impaired growth plate maturation, and in preosteoblasts, MDD slows cellular proliferation. MDD produces a decreased expression of VDR, estrogen receptor-α, PGC1α, PRMT1 and Sirt1 and decreased nuclear VDR-PGC1α interaction [ 99 ]. The weaker VDR-PGC1α interaction is attributed to the reduced expression and imbalanced methylation/acetylation of PGC1α and the nuclear VDR sequestration by heat shock protein 90 (HSP90).…”
Section: Introductionmentioning
confidence: 99%
“…The weaker VDR-PGC1α interaction is attributed to the reduced expression and imbalanced methylation/acetylation of PGC1α and the nuclear VDR sequestration by heat shock protein 90 (HSP90). These mechanisms together compromise bone development, as reflected by lowered bone alkaline phosphatase and increased proadipogenic PPARγ, adiponectin and estrogen-related receptor-α expression [ 99 ].…”
Section: Introductionmentioning
confidence: 99%